Reproductive history and breast cancer risk - Kobayashi, Shunzo (Springer Japan, 2012)
The fact that reproductive factors have significant influence on the risk of breast cancer is well known. Early age of first full-term birth is highly protective against late-onset breast cancers, but each pregnancy, including the first one, increases the risk of early-onset breast cancer. Estradiol and progesterone induce receptor activator of NF-kappa B ligand (RANKL) in estrogen receptor (ER)- and progesterone receptor (PgR)-positive luminal cells. RANKL then acts in a paracrine fashion on the membranous RANK of ER/PgR-negative epithelial stem cells of the breast. This reaction cascade is triggered by chorionic gonadotropin during the first trimester of pregnancy and results in the morphological and functional development of breast tissue. On the other hand, the administration of non-steroidal anti-inflammatory drugs in the early steps of weaning protects against tumor growth through reduction of the acute inflammatory reaction of post lactation remodeling of breast tissue. This is experimental evidence that may explain the short-term tumor-promoting effect of pregnancy. The protective effect of prolonged breast feeding may also be explained, at least in a part, by a reduced inflammatory reaction due to gradual weaning. Delay of first birth together with low parity and short duration of breast feeding are increasing social trends in developed countries. Therefore, breast cancer risk as a result of reproductive factors will not decrease in these countries in the foreseeable future. In this review, the significance of reproductive history with regard to the risk of breast cancers will be discussed, focusing on the age of first full-term birth and post lactation involution of the breast.